2013
DOI: 10.1161/atvbaha.112.301143
|View full text |Cite
|
Sign up to set email alerts
|

Activator Protein-2α Mediates Carbon Monoxide–Induced Stromal Cell–Derived Factor-1α Expression and Vascularization in Ischemic Heart

Abstract: Objective-Increased cardiac stromal cell-derived factor-1α (SDF-1α) expression promotes neovascularization and myocardial repair after ischemic injury through recruiting stem cells and reducing cardiomyocyte death. Previous studies have shown that heme oxygenase-1 and its reaction byproduct, carbon monoxide (CO), induce SDF-1α expression in ischemic heart. However, the mechanism underlying heme oxygenase-1/CO-induced cardiac SDF-1α expression remains elusive. This study aims to investigate the signaling pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…12;164 Work by Lin et al showed that treatment with CO gas or CORM-2 promoted neovascularization and myocardial repair after coronary artery ligation. 125 CO increased the activation of SDF-1 via an Akt-dependent AP-2α expression. Blockade of AP-2α abrogated the beneficial effects of CO treatment.…”
Section: Interaction Of Co With Cellular Targetsmentioning
confidence: 86%
See 1 more Smart Citation
“…12;164 Work by Lin et al showed that treatment with CO gas or CORM-2 promoted neovascularization and myocardial repair after coronary artery ligation. 125 CO increased the activation of SDF-1 via an Akt-dependent AP-2α expression. Blockade of AP-2α abrogated the beneficial effects of CO treatment.…”
Section: Interaction Of Co With Cellular Targetsmentioning
confidence: 86%
“…HO-1 and its products have not been directly examined in the regeneration of heart vessels after IR but can confer protection against vascular injury and inflammation in models of atherosclerosis and vessel injury 113;123 and significantly contribute to neoangiogenesis and neovascularisation 124;125 (see below). Therefore, we can foresee a multifunctional implication of the HO-1 system in IR: 1) as a sensor of cardiac injury and DAMPs; 2) as a modulator of inflammation and the immune response and; 3) as a mediator that aids the repair and reconstruction of cardiac tissue.…”
Section: Ho-1 and Cardiovascular Protectionmentioning
confidence: 99%
“…24 It has been shown that heme oxygenase-1 and its reaction byproduct carbon monoxide can induce CXCL12 expression in the hearts of infarcted mice. 25 A study by Lin et al 26 further elucidated the mechanism behind this carbon monoxide-induced CXCL12 expression and cardioprotection. Applying several in vitro approaches revealed that CXCL12 upregulation by carbon monoxide was mediated by protein kinase B-dependent stimulation of the transcription factor activator protein-2α in cardiomyocytes.…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…Ap-2 proteins have been reported to bind to a highly conserved GC-rich consensus sequence present in numerous cellular and viral promoters and enhancers. An in vitro binding site selection assay identified GCCN3/4GGC and GCCN3/4GGG as the preferred sequence motifs bound by Ap-2 transcription factors (7,8). Two multiple protein-binding sites were identified in the HMOX1 upstream promoter regions, which were HMOX1-1, 5'-agttcctgatgttgcccaccaggctattgctctgagcagc-3' (underlined bases represent similar AP-2-binding sequence) and HMOX1-2, 5'-ctcctctccaccccacactggcccggggcgggctgggcgc-3' (underlined bases represent consensus AP-2-binding sequence).…”
Section: Exogenous Expression Of Ap-2 Robustly Transactivates Hmox1 Amentioning
confidence: 99%
“…The transactivation domains of AP-2 proteins are significantly more divergent, although certain critical residues and a PY motif (XPPXY) are conserved (1)(2)(3)(4)(5)(6). A number of functional AP-2 binding sites, consensus to a palindromic core sequence, 5'-GCCN 3 GGC-3', have been identified in cellular and viral enhancers, and preferred binding to the sequence motifs GCCN 3 GGC, GCCN 4 GGC and GCCN 3/4 GGG was observed in an in vitro binding site selection assay (7,8). The PY motif and critical residues in the transactivation domain, which are considered necessary for transactivation, were divergent in Ap-2δ.…”
Section: Introductionmentioning
confidence: 99%